Reimagining access and sustainable parasiticide innovation for African livestock - Halos, L.; Ameda, B.; Ducrotoy, M.; Kock, L.; Mulongo, Musa M.; Muthee, J.; Vudriko, P.; Howe, M.; Evans, A.; Fletcher, M.; Biguezoton, A.; The Multistakeholder Working Group on Parasiticide Access (Cell Press, 2025)
Livestock is a vital source of nutrition, income, and resilience in Africa, yet parasitic diseases remain a major constraint to productivity. Access to safe, effective, and affordable parasiticides for smallholder farmers is limited, while reliance on outdated or substandard products, rising resistance, counterfeit drugs, and weak regulation further reduce effectiveness. This article summarizes outcomes from a recent multi-stakeholder meeting on parasiticide access, emphasizing that innovation must extend beyond new molecule discovery to include adapted formulations, smart regulation, local delivery models, workforce capacity, diagnostic and product stewardship. Coordinated action by governments, industry, farmers, and animal health professionals is essential to improve access and make parasite control a driver of resilient, equitable, and sustainable livestock systems across Africa.